HUBUNGAN ANTARA KUALITAS PELAYANAN PASIEN RAWAT JALAN DENGAN TINGKAT KEPUASAN DI APOTEK INSTALASI FARMASI RUMAH SAKIT ISLAM SITTI MARYAM KOTA MANADO - Kiyai, Ayu Ashari; Rattu, Angel Heart; Maramis, Franckie; Pangemanan, Jane (Sam Ratulangi University, 2015)
At the present one of challenge in service health at hospital is fullfiling ofexpectation of quality of service pharmacy. The application of medical service, as theintegral part of patient satisfaction and whole medical service activity. Hospital must givebest service to reach satisfaction. Satisfaction of pharmacy services which can be seen from 5(five) servqual dimension (responsiveness, reliability, assurance, empathy, tangibles).Methods : This research is an analytical research survey with a cross sectional researchdesign. Subject of this research is the outpatient in islamic hospital Sitti Maryam. Thenumber of samples in this research were 100 samples. Retrieval of data throughquestionnaires. Statistical tests were used to analyze the relationship between variables usingthe Pearson Product Moment with Î± = 0,05 and CI = 95%.Result : The result of good responsiveness is 47%, good reliability 32%, good assurance29%, good empathy 48%, good tangibles 88%. And the level of patient satisfaction is 42%.The statistic test result from the responsiveness variable with patient satisfaction obtainablerhitung = 0,018; reliability variable with patient satisfaction obtainable rhitung = 0,172;assurance variable with patient satisfaction obtainable rhitung = 0,216; empathy variable withpatient satisfaction obtainable rhitung = 0,265; tangibles variable with patient satisfactionobtainable rhitung = 0,491.Conclusion : The test results indicate that there is a relationship between the pharmacyservice in dimension of assurance, empathy, tangibles with outpatient satisfaction. thedimensions of responsiveness and reliability dimension there is no relationship with patientssatisfaction.Keywords : Quality of pharmacy services, Patients satisfaction